Development and Evaluation of Assessments for Counseling Professionals. (2nd October 2017) - Lenz, A. Stephen; Wester, Kelly L.
ABSTRACT: It is imperative that counselors understand how to critically evaluate assessments before using them to make clinical decisions. This evaluation can be conducted through integrating the 5 sources of validity. Each source of validity is discussed, along with methods to appraise psychometric quality, throughout this special issue.